"Esmeralda" waltz-lanciers. Arranged for the Esmeralda Club, of St. Louis, Mo. - Florence, W. W. (William W.); Esmeralda Club (Saint Louis, Mo.) ([St. Louis? Mo.], 1882)
Created for the Esmeralda Club of Saint Louis, this short pamphlet consists of five figures of a waltz quadrille with a brief explanation of each figure.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Waltz -- Handbooks, manuals, etc; Quadrille (Dance) -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals